Genome-Guided Mass Spectrometry Expedited the Discovery of Paraplantaricin TC318, a Lantibiotic Produced by Lactobacillus paraplantarum Strain Isolated From Cheese - Hussein, Walaa E.; Huang, En; Ozturk, Ismet; Somogyi, Árpád; Yang, Xu; Liu, Baosheng; Yousef, Ahmed E. (Frontiers in Microbiology, 2020)
The quest for potent alternatives to the currently used antimicrobials is urged by health professionals, considering the rapid rise in resistance to preservatives and antibiotics among pathogens. The current study was initiated to search for novel and effective bacteriocins from food microbes, preferably lactic acid bacteria (LAB), for potential use as preservatives. Advances in genome-guided mass spectrometry (MS) were implemented to expedite identifying and elucidating the structure of the recovered antimicrobial agent. A LAB strain, OSY-TC318, was isolated from a Turkish cheese, and the crude extract of the cultured strain inhibited the growth of various pathogenic and spoilage bacteria such as Bacillus cereus, Clostridium sporogenes, Enterococcus faecalis, Listeria monocytogenes, Salmonella enterica ser. Typhimurium, and Staphylococcus aureus. The antimicrobial producer was identified as Lactobacillus paraplantarum using MS biotyping and genomic analysis. Additionally, L. paraplantarum OSY-TC318 was distinguished from closely related strains using comparative genomic analysis. Based on in silico analysis, the genome of the new strain contained a complete lantibiotic biosynthetic gene cluster, encoding a novel lantibiotic that was designated as paraplantaricin TC318. The bioinformatic analysis of the gene cluster led to the prediction of the biosynthetic pathway, amino acid sequence, and theoretical molecular mass of paraplantaricin TC318. To verify the genomic analysis predictions, paraplantaricin TC318 was purified from the producer cellular crude extract using liquid chromatography, followed by structural elucidation using Fourier transform ion cyclotron resonance MS analysis. This genome-guided MS analysis revealed that the molecular mass of paraplantaricin TC318 is 2,263.900 Da, its chemical formula is C106H133N27O22S4, and its primary sequence is F-K-S-W-S-L-C-T-F-G-C-G-H-T-G-S-F-N-S-F-C-C. This lantibiotic, which differs from mutacin 1140 at positions 9, 12, 13, and 20, is considered a new member of the epidermin group in class I lantibiotics. In conclusion, the study revealed a new L. paraplantarum strain producing a novel lantibiotic that is potentially useful in food and medical applications.